Values Education and Lifelong Learning
XVI, 448 p.
Keywords: The aim of this book is to provide an easily accessible, practical yet scholarly source of information about the international concern for the nature, theory and practices of the ideas of values education and lifelong learning. Each chapter in this book is written in an accessible style by an international expert in the field. Authors tackle the task of identifying, analysing and addressing the key problems, topics and issues relevant to questions about the nature, purpose and scope of values education and Lifelong Learning that are internationally generalisable and, in times of rapid change, of enduring interest to the scholar and practitioner. Authors explore the ways and means by which learners may be encouraged to become educated and grow, both as individual beings and social agents, throughout the whole of their lifespan. The book seeks to provide accounts and critical appraisal of some of the different principles, philosophies, theories, beliefs, traditions and cultures that might form the basis of, frame and furnish the setting for values education policies and programs. We look at some of the main theories behind versions of value in lifelong learning and we point to some of the key concepts and categories at work in such theories. We provide reference to and accounts of some examples of policies or proposals in various national contexts and a range of examples of good practice in policies, programs and curriculum schemes from different schools, school systems and other educating agencies, institutions and organisations around the world.